Implications of Enrichment and Poetry Learning on the Cognitive Development of Primary School Students: Implikasi Pengayaan dan Pembelajaran Pantun Terhadap Perkembangan Kognitif Murid Sekolah Rendah - Mohamed, Ros Anita Kartini; Ali, Abdul Halim (Jurnal Pendidikan Bitara UPSI, 2022)
Among the goals of the application of literature in enrichment and learning in primary schools is to strengthen language teaching, instill an interest in reading and emphasize noble values, produce students who think critically and derive lessons from such learning. The application of pantun in primary schools, for example, is believed to help 21st century students in enrichment and learning towards critical thinking. This is because in the pantun are implied moral values ​​that are expressed in daily life. Teaching pantun in teaching also guides students to entertain, interpret and evaluate their phenomena so that children’s emotional intelligence can develop. With its structured nature and easy to manipulate, the pantun seeks to support this role. Descriptive qualitative and literature review methods were used to analyze the pantun in styling and learning in the classroom. Next, the findings of the discussion of this paper are focused on the ability of students to express the author’s thoughts critically concerning children’s lives using Bloom Anderson & Krathwohl’s 2001 Revised Edition Taxonomy theory in learning.